World Literature in the World? Kahf ’s The Girl in the Tangerine Scarf and the Transnational Reading Public - Aghasi, Maya (2021)
Criticized for being too Euro- and Americentric, world literature scholarship tends to center on the American implications of this shortcoming, with little discussion of world literature beyond these centers. This paper thus addresses the function of world literature beyond these centers, particularly in the lingua franca of global business: English. Drawing from my experience in the United Arab Emirates, I argue that because students in the region come from places with fraught colonial histories, migrant, Anglophone literature is critical in the world literature classroom because it allows them to see their own experiences articulated in the global literary vernacular. Using Mohja Kahf’s The Girl in the Tangerine Scarf as an example, I show how its transnational scope addresses both the hegemonic, Euro-American gaze, but also the students’. Thus, Anglophone literature is not necessarily the extension of an imperialist project or a flattening of differences; rather, it becomes an articulation of them.